ONE STAY THREE STRAY: STRATEGI MENINGKATKAN KETRAMPILAN MENULIS JENIS TEKS EKSPOSISI DALAM PEMBELAJARAN GENRE-BASED WRITING - Intan Permata Hapsari; Novia Trisanti; Galuh Kirana Dwi Areni (Universitas Negeri Semarang, 2013)
This is a classroom action research within the context of cooperative learning, which is conducted to investigate how exposition texts are developed through One Stay Three Stray strategy, and how One Stay Three Stray strategy can change students’ positive attitude in writing exposition texts. The study was done towards a class of Genre-based Writing in English Department of Semarang State University. The main goal of this study is to help students improve the way how to communicate their ideas through texts they develop. The problems which the writer deals with to uncover the above phenomena are: (1) How can One Stay Three Stray strategy help students in solving problems dealing with writing and developing their ideas in writing exposition texts? And (2) how does One Stay Three Stray strategy change students’ positive attitude to achieve the goals of the Genre-based Writing Subject, especially in achieving the goal of writing exposition texts? Based on the result of the research, it is found that there is a positive impact on the use of One Stay Three Stray strategy on the teaching and learning process of exposition texts. This can be seen on the result of the evaluation of the process and of the composition produced by students during the research. The students’ writings from the four cycles improve significantly.